Cross species analysis of Prominin reveals a conserved cellular role in invertebrate and vertebrate photoreceptor cells. - Nie, J.; Mahato, S.; Mustill, W.; Tipping, C.; Bhattacharya, S.S.; Zelhof, A.C. (Developmental Biology, 2012)
The two fundamental types of photoreceptor cells have evolved unique structures to expand the apical membrane to accommodate the phototransduction machinery, exemplified by the cilia-based outer segment of the vertebrate photoreceptor cell and the microvilli-based rhabdomere of the invertebrate photoreceptor. The morphogenesis of these compartments is integral for photoreceptor cell integrity and function. However, little is known about the elementary cellular and molecular mechanisms required to generate these compartments. Here we investigate whether a conserved cellular mechanism exists to create the phototransduction compartments by examining the functional role of a photoreceptor protein common to both rhabdomeric and ciliated photoreceptor cells, Prominin. First and foremost we demonstrate that the physiological role of Prominin is conserved between rhabdomeric and ciliated photoreceptor cells. Human Prominin1 is not only capable of rescuing the corresponding rhabdomeric Drosophila prominin mutation but also demonstrates a conserved genetic interaction with a second photoreceptor protein Eyes Shut. Furthermore, we demonstrate the Prominin homologs in vertebrate and invertebrate photoreceptors require the same structural features and post-translational modifications for function. Moreover, expression of mutant human Prominin1, associated with autosomal dominant retinal degeneration, in rhabdomeric photoreceptor cells disrupts morphogenesis in ways paralleling retinal degeneration seen in ciliated photoreceptors. Taken together, our results suggest the existence of an ancestral Prominin-directed cellular mechanism to create and model the apical membranes of the two fundamental types of photoreceptor cells into their respective phototransduction compartments.